Rancang Bangun Aplikasi Augmented Reality Sebagai Media Promosi Model Tatanan Rambut Pada Barbershop Berbasis Android - Karda, Putu Adistyanda Timoti Raja; Suyadnya, I Made Arsa; Khrisne, Duman Care (LPPM STMIK STIKOM Indonesia, 2018)
The development of barbershop makes business competition becomes increasingly tight. Currently, information and communication technology is very important in the field of barbershop marketing. But this technology only shows details of the existence of barbershop. In addition, the catalog of hairstyles that are provided only in the form of 2-dimensional images. Therefore, more advanced technology is needed to promote the model of hairstyle available in barbershop. One of the technology applied in smartphone applications is Augmented Reality on the Android operating system. In this research will be developed an Augmented Reality based promotion media to promote hair model model with 3 dimensional object visualization using marker based tracking method. Development of this application starts from the stage of concept creation, application design, 3-dimensional object creation, application assembly, application testing, until the application distribution stage. This application was created using C # programming language, Vuforia Qualcomm, virtual and Unity Autodeks Maya software. The application that has been produced is tested by 2 methods that is by black-box testing and by usability scale system test, on the test of black -box AugmentedReality application of functional barbershop that exist in the application has been successfully executed according to their respective function. Based on survey results on Usabilty ScaleSystem(SUS) test on Augmented Reality Barbershop application, 20 respondents gave average score of 73.35 with Grade Scale C.